Development and Characterization of the NanoOrange® Protein Quantitation Assay: A Fluorescence-Based Assay of Proteins in Solution - Laurie J. Jones; Richard P. Haugland; Victoria L. Singer (BioTechniques)
We developed a sensitive fluorescence assay for the quantitation of proteins in solution using the NanoOrange® reagent, a merocyanine dye that produces a large increase in fluorescence quantum yield upon interaction with detergent-coated proteins. The NanoOrange assay allowed for the detection of 10 ng/mL to 10 μg/mL protein with a standard fluorometer, offering a broad, dynamic quantitation range and improved sensitivity relative to absorption-based protein solution assays. The protein-to-protein variability of the NanoOrange assay was comparable to those of standard assays, including Lowry, bicinchoninic acid, and Bradford procedures. We also found that the NanoOrange assay is useful for detecting relatively small proteins or large peptides, such as aprotinin and insulin. The assay was somewhat sensitive to the presence of several common contaminants found in protein preparations such as salts and detergents; however, it was insensitive to the presence of reducing agents, nucleic acids, and free amino acids. The simple assay protocol is suitable for automation. Samples are briefly heated in the presence of dye in a detergent-containing diluent, allowed to cool to room temperature, and fluorescence is measured using 485-nm excitation and 590-nm emission wavelengths. Therefore, the NanoOrange assay is well suited for use with standard fluorescence microplate readers, fluorometers, and some laser scanners.